Sucrose‐nitrate auto combustion synthesis of Ce0.85Ln0.10Sr0.05O2‐δ (Ln = La and Gd) electrolytes for solid oxide fuel cells. (13th February 2020) - Vijaykumar, Vishnu; Nirala, Gurudeo; Yadav, Dharmendra; Kumar, Upendra; Upadhyay, Shail
Summary: Nanocrystalline powders of co‐doped ceria oxides Ce0.85 La0.10 Sr0.05 O2‐ δ (CLSO) and Ce0.85 Gda0.10 Sr0.05 O2‐ δ (CGSO) have been synthesized by auto combustion method at 100°C using sucrose as fuel. Thermal analysis (TGA/DSC) of as‐prepared powders indicated calcination above 400°C to remove organic residue. The average grain size of the pellets sintered at 1200°C for 4 hours is 436 and 683 nm for CLSO and CGSO, respectively. The electrical conductivity of the sintered samples was determined by impedance measurements in the temperature range 300°C to 600°C and the frequency range 20 Hz to 2 MHz. At 600°C, the total electrical conductivity ( σ t ) of CGSO is 6.78 × 10 −3 S cm −1, 2.5 times higher than 2.72 × 10 −3 S cm −1 of CLSO. Further, it is found that the value of grain boundaries blocking factor ( α gb ) of CGSO is 0.47 which is 30% lesser than 0.68 of CLSO at 600°C. The higher value of electrical conductivity of CGSO as compared to CLSO is attributed to the lesser blocking effect of grain boundaries, smaller lattice distortion and denser microstructure of CGSO as compared to CLSO. The electrical conductivity of synthesized samples has been compared with the electrical conductivity of similar compositions of co‐doped CeO2 oxides. Our study indicated that the sintering temperature, and hence, the morphology of sintered samples has a significant role in determining the electrical conductivity. The presence of oxygen vacancies in the synthesized samples is experimentally supported by using UV‐visible spectroscopy, Raman spectroscopy, and thermal analysis techniques. Abstract : XRD and electrical conductivity